Taxonomy and pathogenicity of fungi associated with oak decline in northern and central Zagros forests of Iran with emphasis on coelomycetous species - Bashiri, Samaneh; Abdollahzadeh, Jafar (Frontiers in Plant Science, 2024)
Oak decline as a complex disorder seriously threatens survival of Zagros forests. In an extensive study on taxonomy and pathology of fungi associated with oak decline in central and northern part of Zagros forests, 462 fungal isolates were obtained from oak trees showing canker, gummosis, dieback, defoliation and partial or total death symptoms. Based on ISSR fingerprinting patterns, morphological characteristics and sequences of ribosomal DNA (28S rDNA and ITS) and protein coding loci (acl1, act1, caMm, rpb1, rpb2, and tub2) 24 fungal species corresponded to 19 genera were characterized. Forty percent (40%) of the isolates placed in eight coelomycetous species from seven genera, namely Alloeutypa, Botryosphaeria, Cytospora, Didymella, Gnomoniopsis, Kalmusia and Neoscytalidium. Of these, four species are new for science which are introduced here as taxonomic novelties; Alloeutypa iranensis sp. nov., Cytospora hedjaroudei sp. nov., Cytospora zagrosensis sp. nov. and Gnomoniopsis quercicola sp. nov. According to pathogenicity trials on leaves and stems of 2-year-old Persian oak (Quercus brantii) seedlings Alternaria spp. (A. alternata, A. atra and A. contlous), Chaetomium globosum and Parachaetomium perlucidum were recognized as nonpathogenic. All coelomycetous species were determined as pathogenic in both pathogenicity triaails on leaves and seedling stems, of which Gnomoniopsis quercicola sp. nov., Botryosphaeria dothidea and Neoscytalidium dimidiatum were highly pathogenic and recognized as the most pathogenic virulent species followed by Biscogniauxia rosacearum. woody plants including coelomycetous fungi, a well-known morphological group belonging to the class Dothideomycetes (Wijayawardene et al., 2016). The most common pathogenic coelomycetous fungal species in association with declined trees showing canker, gummosis, dieback, wilting and wood discoloration and necrosis are members of the Botryosphaeriaceae (e.g. Botryosphaeria, Diplodia,